1985
DOI: 10.1111/j.1527-3466.1985.tb00481.x
|View full text |Cite
|
Sign up to set email alerts
|

Milrinone

Abstract: CHEMICAL AND PHYSICAL PROPERTIESMilrinone (Win 47203) is 1,6-dihydro-2-methyl-6-0~0-(3,4'-bipyridine)-5-carbonitrile ( Fig. 1). It is a tan, nonhygroscopic, nonsolvated, polymorphic crystalline powder soluble in dilute acids. Its molecular formula is CI2H9NO3 and its molecular weight is 211.2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 92 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…Although milrinone is more potent than amrinone, the pharmacology of these two drugs with respect to their positive inotropic and vasodilatory effects has been quite comparable (3). The mechanism of the cardiotonic action of these bipyridine compounds is not fully understood, but most current evidence suggests that their effects are due to inhibition of specific phosphodiesterase activity (22,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although milrinone is more potent than amrinone, the pharmacology of these two drugs with respect to their positive inotropic and vasodilatory effects has been quite comparable (3). The mechanism of the cardiotonic action of these bipyridine compounds is not fully understood, but most current evidence suggests that their effects are due to inhibition of specific phosphodiesterase activity (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Amrinone inhibited macromolecular synthesis in bone tissue, which could explain some but not all of the observed effects (2). Milrinone (2-methyl-5-cyano- [3,4'-bipyridine]-6[ lH]-one) is an analog of amrinone that differs only in the addition ofa methyl group and the replacement of a cyano for an amino group on one pyridine ring of the drug (3). Milrinone has been reported to be a more potent cardiotonic agent with lower toxicity than amrinone.…”
Section: Introductionmentioning
confidence: 99%
“…In healthy subjects, milrinone has been reported to be mainly excreted in the urine in two forms: unchanged (83%) and as an O-glucuronic acid conjugate (12%) (Primacor®, n.d.). Alousi et al (1985) reported a similar mean extent of glucuronidation in dogs using radioactive compounds and separation by HPLC (15 %). Therefore, determination of the total amount of milrinone excreted in urine after nebulization would allow us to assess the systemic bioavailability after this highly variable route of administration.…”
Section: Introductionmentioning
confidence: 73%
“…A mean extent of 12% for O-glucuronidation has been reported in healthy volunteers (Primacor®, n.d.). Alousi et al (1985) reported using a mild acid hydrolysis without providing a description of the incubation conditions nor of the between-subject variability in the content of the glucuronic acid conjugate.…”
Section: Clinical Applicationmentioning
confidence: 99%